TGA factors promote plant root growth by modulating redox homeostasis or response. Issue 8 (8th July 2022) - Hu, Xiaochen; Yang, Liyun; Ren, Mengfei; Liu, Lin; Fu, Jing; Cui, Hongchang
Abstract: To identify novel regulators of stem cell renewal, we mined an existing but little explored cell type‐specific transcriptome dataset for the Arabidopsis root. A member of the TGA family of transcription factors, TGA8, was found to be specifically expressed in the quiescent center (QC). Mutation in TGA8 caused a subtle root growth phenotype, suggesting functional redundancy with other TGA members. Using a promoter:: HGFP transgenic approach, we showed that all TGA factors were expressed in the root, albeit at different levels and with distinct spatial patterns. Mutant analyses revealed that all TGA factors examined contribute to root growth by promoting stem cell renewal, meristem activity, and cell elongation. Combining transcriptome analyses, histochemical assays, and physiological tests, we demonstrated that functional redundancy exists among members of clades II and V or those in clades I and III. These two groups of TGA factors act differently, however, as their mutants responded to oxidative stress differently and quantitative reverse transcription polymerase chain reaction assays showed they regulate different sets of genes that are involved in redox homeostasis. Our study has thus uncovered a previously unrecognized broad role and a mechanistic explanation for TGA factors in root growth and development. Abstract : In addition to their well‐known roles in defense against pathogens, TGA transcription factors are also important for root growth and development, attributable to a role in modulating redox homeostasis. Although functionally similar, these TGA factors exhibit distinct expression patterns and modes of action.